ANALISIS BIAYA PRODUKSI KAYU GERGAJIAN PADA PT KATINGAN TIMBER CELEBES DESA WAMLANA KABUPATEN BURU - Fitri N.S. Ellis; Troice E. Siahaya; Mersiana Sahureka (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2020)
The objective of this study was to find out components of production cost and analyzing the cost of production materials which used full costing method and variable costing method. This research was conducted at October 2019 on PT. Katingan Timber Celebes Wamlana Village, Fenaleisela Subdistrict, Buru Regency. The company is a buried sawmill industry at Buru Island when has a primary industrial license for timber. Research data were collected by observation, documentation and interview methods, and then analyzed by full costing and variable costing methods. The result showed that the components of production cost consist of raw materials cost, direct labor cost used fixed factory overhead cost and variable factory overhead cost. The cost of production used costing method have value of Rp.5.120.341.644,- more higher compered to variable costing is Rp.4.542.320.899,- the difference value of the cost of production due to full costing methods which imposes the fixed overhead cost and the variable overhead cost, that the cost of production is higher than with variable costing methods which imposes by factory overhead cost.